Conceptual insights into the diverse pathways in migrant entrepreneurship - Aleksandra Gaweł; Katarzyna Mroczek-Dąbrowska; Agnieszka Głodowska; Krzysztof Wach (International Entrepreneurship Review)
Objective: The objective of the article is to conceptualize and systematize the most relevant dimensions and issues of migrant entrepreneurship based on the literature review.